Benefit-Entitlement Effects and the Duration of Unemployment An Ex-ante Evaluation of Recent Labour Market Reforms in Germany - Hendrik Schmitz; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
We analyse benefit-entitlement effects and the likely impact of the recent reform of the unemployment compensation system on the duration of unemployment in Germany on the basis of a flexible discrete-time hazard rate model estimated on pre-reform data from the German Socioeconomic Panel (SOEP). We find (i) relatively strong benefit-entitlement effects for the unemployed who are eligible to means-tested unemployment assistance after the exhaustion of unemployment benefit, but not for those without such entitlement; (ii) non-monotonic benefit-entitlement effects on hazard rates with pronounce spikes around the month of benefit-exhaustion, and (iii) relatively small marginal effects of the amount of unemployment compensation on the duration of unemployment. Our simulation results show that the recent labour market reform is unlikely to have a major impact on the average duration of unemployment in the population as a whole, but will significantly reduce the level of long-term unemployment among older workers.
Keywords: H31; J65; J64; 330; unemployment duration; unemployment insurance; benefit-entitlement effects; German labour market reforms; ex-ante evaluation; hazard rate model; Arbeitslosenversicherung; Reform; Langzeitarbeitslosigkeit; Deutschland